Atrial electromechanical delay in patients undergoing heart transplantation. Issue 2 (14th September 2016) - Bulut, Mustafa; Evlice, Mert; Celik, Mehmet; Eren, Hayati; Savluk, Ömer F.; Acar, Rezzan D.; Tabakci, Mustafa; Emiroglu, Mehmet Y.; Otcu (Nurse), Ozlem; Kargin, Ramazan; Balkanay, Mehmet; Akcakoyun, Mustafa
Abstract: Background: We aimed to assess atrial electromechanical delay (AEMD) in patients who had undergone heart transplantation. Methods: A total of 32 patients who underwent biatrial anastomosis heart transplantation (24 men, 8 women; mean age: 42±11 years) and 30 healthy volunteers (20 men, 10 women; mean age: 36±13 years) were included in the study. Atrial electromechanical coupling (PA), intra‐AEMD, and inter‐AEMD were measured. Results: PA lateral (68±7 vs. 51±11 ms, p <0.01), PA septal (50±5 vs. 42±8 ms, p < 0.01) and PA tricuspid (39±6 vs. 36±9 ms, p <0.01), inter‐AEMD (PA lateral–PA tricuspid) (27±7 vs. 10±4 ms, p <0.01), left intra‐AEMD (PA lateral–PA septal) (18±7 vs. 10±4 ms, p <0.01), right intra‐AEMD (PA septal–PA tricuspid) (13±5 vs. 5±3 ms, p <0.01) values were higher in patients who underwent heart transplantation than in a control population. Conclusion: Inter‐AEMD and intra‐AEMD were prolonged in patients who underwent heart transplantation as compared to a control population. This may explain the increased atrial fibrillation and other atrial arrhythmia incidences associated with the biatrial anastomosis heart transplantation technique and may contribute to the treatment of atrial fibrillation in this special patient group.